Impaired mRNA Expression of the Migration Related Chemokine Receptor CXCR4 in Mesenchymal Stem Cells of COPD Patients. (19th July 2017) - Karagiannis, K.; Proklou, A.; Tsitoura, E.; Lasithiotaki, I.; Kalpadaki, C.; Moraitaki, D.; Sperelakis, I.; Kontakis, G.; Antoniou, K. M.; Tzanakis, N.
Abstract : Defective tissue repair and remodeling are main aspects of Chronic Obstructive Pulmonary Disease (COPD) pathophysiology. Bone marrow mesenchymal stem cells (BM-MSCs) have been implicated in this direction, as their functional impairment and recruitment could possibly contribute to disease development and progression. The present study characterizes for the first time the expression of migration related chemokine receptors and their ligands in BM-MSCs from COPD patients. CXCR4/SDF1a and CCR7/CCL19-CCL21 mRNA levels were evaluated in BM-MSCs obtained from twelve COPD patients and seven healthy donors. SDF1a protein levels in sera and BM-MSCs' conditioned media were also evaluated. CXCR4, SDF1a, CCL19, and CCL21 mRNA levels were significantly reduced in COPD BM-MSCs while CCR7 levels were undetectable. Notably, SDF1a protein levels were marginally elevated in both patient sera and BM-MSCs' conditioned media while the increase in SDF1a serum levels significantly correlated with disease severity in COPD. Our findings show posttranscriptional regulation of SDF1a levels in BM-MSCs of COPD patients and significant downregulation of SDF1a and CXCR4 mRNA indicating an involvement of the SDF1a signaling pathway in the disease pathophysiology.